9514 1404 393
Answer:
(x, y) → (-∞, -∞), (+∞, +∞)
Step-by-step explanation:
The expression is of odd degree with a positive leading coefficient. It will have a generally upward slope (/). That is, the sign of f(x) will match the sign of x for large-magnitude values of x:
x → -∞, f(x) → -∞
x → ∞, f(x) → ∞
Short leg = x-6m
Longer leg =x
Hypotenuse = x+6m
x² + (x-6)² =(x+6)²
x² + x²-12x+36 = x²+12x+36
2x²-12x+36= x² +12x+36
2x²-12x+36-36= x² +12x+36-36
2x² - 12x-12x = x²+12x-12x
2x² -24x-x² = x²-x²
x² -24x = 0
x(x-24)=0
x = 24
Short leg = 24-6m = 18
Longer leg =24
Hypotenuse = 24+6m=30
Check
a² + b² = c²
18² +24² =30²
324 +576 = 900
900=900
You just have to make 36/10 into 3 6/10. After that, it would become 3.6
Answer:
MN=23
Step-by-step explanation:
For the midsegment:
MN=(WZ+XY)/2
10x+3=(11+8x+19)/2
10x+3=4x+15
6x=12
x=2
MN=10×2+3=23